The Relationship Between Pre-Marital Counseling and Healthy Pregnancy Preparation among Prospective Brides and Grooms at the UPTD Puskesmas Malaka, Soppeng Regency - Gaiya, Indar; Nasrayanti; Jaya, Fitri (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction Pre-marital counseling is a health assessment conducted by healthcare professionals, such as midwives, before marriage to ensure proper planning and preparation for a healthy pregnancy. A lack of knowledge regarding reproductive health among prospective brides and grooms can lead to unplanned pregnancies and various pregnancy-related complications. The objective of this study was to analyze the relationship between the implementation of pre-marital counseling and healthy pregnancy preparation at the UPTD Puskesmas Malaka, Soppeng Regency. The method of a univariate analysis was conducted, involving the examination of two variables simultaneously to assess the potential correlation between them. This research employed an analytical survey method with a cross-sectional approach. The study population consisted of 39 prospective brides and grooms who received services at UPTD Puskesmas Malaka, Soppeng Regency. Data were collected using questionnaires and analyzed with the chi-square test. The result of the 26 individuals who received pre-marital counseling, 24 (61.5%) agreed with healthy pregnancy preparation, 2 (5.1%) were uncertain, and none (0%) disagreed. Among the 13 respondents who did not receive pre-marital counseling, 4 (10.3%) agreed with healthy pregnancy preparation, 7 (17.9%) were uncertain, and 2 (5.1%) disagreed. The p-value was 0.000, which is less than 0.05, indicating that H0 is rejected and H1 is accepted. Therefore, it can be concluded that there is a significant relationship between pre-marital counseling and healthy pregnancy preparation. The conclusion was a significant relationship exists between pre-marital counseling and healthy pregnancy preparation